ANALISIS PERAN KELUARGA DALAM MEMBENTUK KARAKTER ANAK USIA 6-12 TAHUN - Jadidah, Ines Tasya; Wijaya, Henni; Darma, Ain Doe; Anggilin, Kaliana; Halizah, Rheina Nur (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2023)
A person's character is the quality he has that has the power to direct things such as his thoughts, behavior and overall character. Character is a set of behavioral principles related to God, oneself, other people and the environment. The problem raised in this research is how parents respond to their children's mistakes and how to educate their behavior at home. Descriptive methods and qualitative approaches were used in this research. The findings of this study show how important families are in helping children develop their moral character. A child in elementary school, aged 6 to 12 years, receives education primarily from his family. Families have a responsibility to help shape the character of their generation by providing good examples and caring for their offspring from childhood. This includes teaching virtues, having good conversations with children, modeling positive behavior, and not abusing their power to the point of causing trauma. Fathers are as important in shaping their children's character as the mother's role in providing education for their children.